The effect of visual stimuli and its quality on the design creativity of architecture students - Mahmood reza Saghafi; Mohammad ali Aashraf ganjooie (آموزش مهندسی ایران, 2016)
Although visual stimuli have a great influence on design creativity, there are few studies in the education of architectural design courses focusing on this topic. The aim of this research is to study the effects of visual stimuli on improving students' creativity in design courses. The results of this research can be used by design course teachers. The hypothesis is that different qualities of stimuli have varied effects on student creativity in architectural design courses. An empirical study was done with architecture students (who had passed up to four design courses). They were divided into three groups. Two groups did a design task with different stimuli (rich stimuli for one group and an ambiguous sketch for the another). The third group did the same task without any stimuli. Three judges evaluated the creativity of the design solutions according to novelty and practicality. The scores were analyzed by ANOVA. The findings revealed the effects of visual stimuli on the creativity of design product and suggested that different types of visual stimuli have different effects on the practicality and originality of the products.